2015
DOI: 10.1038/nplants.2015.94
|View full text |Cite
|
Sign up to set email alerts
|

V-ATPase activity in the TGN/EE is required for exocytosis and recycling in Arabidopsis

Abstract: In plants, vacuolar H + -ATPase (V-ATPase) activity acidifies both the trans-Golgi network/early endosome (TGN/EE) and the vacuole. This dual V-ATPase function has impeded our understanding in how the pH homeostasis within the plant TGN/EE controls exo-and endocytosis.⋆ Staffan. Persson@unimelb.au.edu, karin.schumacher@cos.uni-heidelberg.de, and eugenia.russinova@psb.vib-ugent. Additional informationSupplementary information is available on line. Competing interestsThe authors declare no competing financial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(163 citation statements)
references
References 48 publications
9
152
2
Order By: Relevance
“…lower TGN pH values of 5.6 and 6.1 have been reported by other groups (Martinière et al, 2013;Luo et al, 2015).…”
Section: Proton Pumps and Leaks: Tgn Ph Is Essentialmentioning
confidence: 48%
See 1 more Smart Citation
“…lower TGN pH values of 5.6 and 6.1 have been reported by other groups (Martinière et al, 2013;Luo et al, 2015).…”
Section: Proton Pumps and Leaks: Tgn Ph Is Essentialmentioning
confidence: 48%
“…In plant cells, interfering with the TGN-resident VHA-a1 isoform causes the swelling of Golgi cisternae and inhibits cell expansion and hypocotyl growth (Dettmer et al, 2006;Brüx et al, 2008). Mutants with reduced activity of the cytosolic VHA-c subunit alter the steady-state pH in the TGN/EE, leading to reduced motility of both Golgi and TGN and defects in secretion of the brassinosteroid receptor BRI1 and Cellulose Synthase (Luo et al, 2015). Curiously, the TGN/EE-localized V-ATPase seems to contribute via an undefined mechanism to vacuolar pH (Kriegel et al, 2015).…”
Section: Proton Pumps and Leaks: Tgn Ph Is Essentialmentioning
confidence: 99%
“…pH-dependent cleavage and degradation of the propeptide was also reported for some mammalian PCs and has been well studied in furin, where it provides a mechanism for compartment-specific activation of the protease (26,29). Similarly in SBT3, pH dependence of PP cleavage may prevent precocious activation and ensure that the active enzyme is not released before the pH drops along the secretory pathway from pH 6.3 in trans-Golgi cisternae to pH 5.6 in the trans-Golgi network/ early endosome (45).…”
Section: Function Of Propeptides In Plant Subtilasesmentioning
confidence: 99%
“…An alternative explanation would be that vesicular trafficking from the TGN/EE to the vacuole delivers a substantial amount of protons and/or organic acids to the vacuolar lumen. The TGN/EE is the most acidic compartment of the plant endomembrane system (Martinière et al, 2013;Shen et al, 2013), and using a pH-sensor with suitable resolution at low pH, we have recently shown that in Arabidopsis roots pH in the TGN/EE is indeed lower than the vacuolar pH (Luo et al, 2015). At least three independent, parallel trafficking pathways exist from the TGN/EE to the vacuole (Pedrazzini et al, 2013;Rojas-Pierce, 2013), and it remains to be determined if the combined flux of protons delivered to the vacuolar lumen would be sufficient to maintain a proton gradient even in the absence of tonoplast-localized proton pumps.…”
Section: How Can Vacuoles Be Acidic Without V-atpase and V-ppase?mentioning
confidence: 99%